High-Mobility Group Nucleosome-Binding Protein 1 as Endogenous Ligand Induces Innate Immune Tolerance in a TLR4-Sirtuin-1 Dependent Manner in Human Blood Peripheral Mononuclear Cells - Arts, Rob J. W.; Huang, Po-Kai; Yang, De; Joosten, Leo A. B.; van der Meer, Jos W. M.; Oppenheim, Joost J.; Netea, Mihai G.; Cheng, Shih-Chin (Frontiers in Immunology, 2018)
HMGN1 (High-mobility group Nucleosome-binding protein 1) functions as a non-histone chromatin-binding protein in the cell nucleus. However, extracellular HMGN1 acts as an endogenous danger-associated inflammatory mediator (also called alarmin). We demonstrated that HMGN1 not only directly stimulated cytokine production, but also had the capacity to induce immune tolerance in a TLR4 dependent pathway, similar to lipopolysaccharide (LPS)-induced tolerance. HMGN1-induced tolerance was accompanied by a metabolic shift associated with the inhibition of the induction of Warburg effect (aerobic glycolysis) and histone deacetylation via Sirtuin-1. In addition, HMGN1 pre-challenge of mice also downregulated TNF production similar to LPS induced tolerance in vivo. In conclusion, HMGN1 is an endogenous TLR4 ligand that can induce both acute stimulation of cytokine production and long-term tolerance, and thus it might play a modulatory role in sterile inflammatory processes such as those induced by infection, trauma or ischemia.